2014
DOI: 10.1002/app.41412
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dianhydrides on the thermal behavior of linear and crosslinked polyimides

Abstract: To determine the thermal characteristics of linear and crosslinked polyimides (PIs), BTDA, ODPA, and 6FDA were used to synthesize polyimides. Thermal degradation temperature and glass transition temperature of the resulting PIs were measured using thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). To measure the change in modulus and coefficient of thermal expansion (CTE) depending on dianhydride structure, a dynamic mechanical analyzer (DMA) and thermo-mechanical analyzer (TMA) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
1
13
0
1
Order By: Relevance
“…In our previous study, we have confirmed the behavior on change of dianhydrides with the property of the NE crosslinked PI . However, the mechanism of norbornene crosslinking has not been elucidated precisely.…”
Section: Introductionsupporting
confidence: 61%
“…In our previous study, we have confirmed the behavior on change of dianhydrides with the property of the NE crosslinked PI . However, the mechanism of norbornene crosslinking has not been elucidated precisely.…”
Section: Introductionsupporting
confidence: 61%
“…It is noteworthy that the aggregation structure of PI film is intensely affected by the variables that control the thermal‐curing process, e.g. temperature and time, which in turn would directly play a critical role in dictating mechanical and thermal properties . It was expected that thermal transitions and concomitant morphology changes caused by the thermal‐activated, free‐radical‐predominant curing of phenylethynyl functional group under various processing conditions should be indicative of the curing behavior and mechanical response of PI films.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism involved in the change of glass transition is probably related to the strong interaction between nanostructured titanates and polyimide resulting in more restriction in polymer chains mobility via steric hindrance. Also, strong covalent bond may occur between hydroxyl group on the surface of titanate nanotube and amino group of polyamic acid during imidization resulting in branching the polymer chain and leading to crosslinking, which usually increases the glass transition temperature in polyimide …”
Section: Resultsmentioning
confidence: 99%